2000
DOI: 10.2135/cropsci2000.4041070x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Season Soybean Yield Compensation in Response to Population and Water Regime

Abstract: Short‐season soybean [Glycine max (L) Merr.] production systems, such as double cropping and late sowing, require high populations to optimize yield, but effects of high populations on seed number and seed mass are unknown. We evaluated plant population effects on yield compensation, stability of harvest index, assimilate partitioning for seed number, and seed‐filling characteristics for 2 yr near Keiser, AR. The study had two cultivars, two levels of irrigation, and three row spacings that each had five level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
82
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 25 publications
11
82
2
2
Order By: Relevance
“…Although some have reported mild adverse effects of drought on seed per pod (Ramseur et al, 1984;Pandey et al, 1984), others have shown no effect (Lawn, 1982;Elmore et al, 1988). In contrast, consistent reports have shown pod m -2 is reduced by drought during the R1-R6 seed formation period (Sionit and Kramer, 1977;Ramseur et al, 1984;Pandey et al, 1984;Snyder et al, 1982;Neyshabouri and Hatfield, 1986;Cox and Jolliff, 1986;Ball et al, 2000). Based on these results, we conclude that reduced seed m -2 from drought stress is derived predominately from reduced pod m -2 rather than seed per pod.…”
Section: Drought Stress and Yieldsupporting
confidence: 56%
See 3 more Smart Citations
“…Although some have reported mild adverse effects of drought on seed per pod (Ramseur et al, 1984;Pandey et al, 1984), others have shown no effect (Lawn, 1982;Elmore et al, 1988). In contrast, consistent reports have shown pod m -2 is reduced by drought during the R1-R6 seed formation period (Sionit and Kramer, 1977;Ramseur et al, 1984;Pandey et al, 1984;Snyder et al, 1982;Neyshabouri and Hatfield, 1986;Cox and Jolliff, 1986;Ball et al, 2000). Based on these results, we conclude that reduced seed m -2 from drought stress is derived predominately from reduced pod m -2 rather than seed per pod.…”
Section: Drought Stress and Yieldsupporting
confidence: 56%
“…pod and seed numbers produced during the emergence to R6 period were reduced by the lower CGR so that seed size (produced during the R5 to R7 seed filling period) could remain constant. Plant population studies conducted under short-season conditions also have outlined a yield-control mechanism very similar to those described for narrow vs. wide row spacing and shade (Ball et al, 2000(Ball et al, , 2001Purcell, 2002). Increasing plant population above the normal recommendation of 25-35 plant m -2 increased LI early in the vegetative period [similar to the findings for narrow vs. wide row spacing ] resulting in an accelerated CGR during the R1 to R5 period, greater dry matter accumulation, and yield (Ball et al, 2000).…”
Section: Light Interception and Yield: Row Spacing And Plant Populationmentioning
confidence: 66%
See 2 more Smart Citations
“…The increase of plant population reduce yield of individual plants but increases yield per unit of area (RA Ball et al, 2000).…”
Section: Introductionmentioning
confidence: 99%